Ultrasound and MR muscle imaging in new onset idiopathic inflammatory myopathies at diagnosis and after treatment: a comparative pilot study. (10th May 2022) - Walter, Anne W; Lim, Johan; Raaphorst, Joost; Smithuis, Frank F; den Harder, J Michiel; Eftimov, Filip; Potters, Wouter; Saris, Christiaan G J; de Visser, Marianne; van Schaik, Ivo N; de Haan, Rob J; van der Kooi, Anneke J; et al.
Abstract: Objectives: To prospectively compare ultrasound (US) and whole-body MRI for detection of muscle abnormalities compatible with idiopathic inflammatory myopathies (IIM). Methods: Newly diagnosed IIM patients underwent US (14 muscles) and MRI (36 muscles) at diagnosis and after nine weeks monotherapy with intravenous immunoglobulin. Muscles were compatible with IIM when quantitative US echo-intensity (EI) z scores was ≥1.5, semi-quantitative US Heckmatt score was ≥2, qualitative US was abnormal, or when MRI showed oedema on T2-weighted images. At patient level, findings were classified as abnormal when quantitative US EI z scores was >1.5 ( n = 3 muscles), >2.5 ( n = 2 muscles) or >3.5 ( n = 1 muscle), or if ≥3 muscles showed abnormalities as described above for the other diagnostic methods. Results: At diagnosis, in 18 patients US of 252 muscles revealed abnormalities in 36 muscles (14%) with quantitative, in 153 (61%) with semi-quantitative and in 168 (67%) with qualitative analysis. MRI showed oedema in 476 out of 623 muscles (76%). Five patients (28%) reached abnormal classification with quantitative US, 16 (89%) with semi-quantitative and qualitative US, and all patients (100%) with MRI. Nine-week follow-up of 12 patients showed no change over time with quantitative US or MRI, and a decrease in abnormalities with semi-quantitative US ( P <0.01), and qualitative US ( P <0.01). Conclusion: At diagnosis, MRI was more sensitive than US to detect muscle abnormalities compatible with IIM. Semi-quantitative US and qualitative US detected abnormalities in the majority of the patients while evaluating fewer muscles than MRI and showed change over time after nine weeks of treatment.